The relevance of social and commercial determinants for neurological health. Issue 12 (December 2022) - Walsh, Sebastian; Merrick, Richard; Brayne, Carol
Summary: A disconnect has developed over the past two decades between neurological and neuroscientific research, which have seen notable innovation and development, and our increasing understanding of the role of social and commercial determinants of health, including the health of the nervous system. Over the next two decades, grounding neurological research in public health and epidemiological principles can bring about a paradigm shift, away from reductionism, over-medicalisation, and health inequities towards neurological research that reduces inequalities and has true relevance to the populations it aims to serve. People who are involved in neurological and neuroscientific research and practice, as clinicians, researchers, publishers, and funders, can create change by being more aware of the social and commercial determinants of health, reprioritising research funding, and advocating for greater neurological health equity.